2017
DOI: 10.1007/s00467-017-3639-y
|View full text |Cite
|
Sign up to set email alerts
|

Longer duration of obesity is associated with a reduction in urinary angiotensinogen in prepubertal children

Abstract: A higher duration of obesity was associated with decreased U-AGT in boys, thus reflecting decreased intrarenal activity of the renin-angiotensin system. Also, children with a longer duration of obesity showed an inverse association between urinary HO and P-AGT. Future studies should address whether these results reflect an early compensatory mechanism to limit obesity-triggered renal dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…We here showed that SCr values of children with overweight and obesity are within the reference range. While some studies have demonstrated similar SCr values between children with lean weight and overweight or obesity [32][33][34][35], in other studies [36,37], SCr values were higher in children with overweight or obesity compared to lean controls. It is not excluded that these inconsistent results are due to confounding factors such as age, height, and sex and/or due to the heterogeneity of the methods for SCr measurements.…”
Section: Discussionmentioning
confidence: 96%
“…We here showed that SCr values of children with overweight and obesity are within the reference range. While some studies have demonstrated similar SCr values between children with lean weight and overweight or obesity [32][33][34][35], in other studies [36,37], SCr values were higher in children with overweight or obesity compared to lean controls. It is not excluded that these inconsistent results are due to confounding factors such as age, height, and sex and/or due to the heterogeneity of the methods for SCr measurements.…”
Section: Discussionmentioning
confidence: 96%
“…Urinary excretion of H2O2 (U-H2O2) was evaluated by a microplate fluorimetric assay (Amplex Red Hydrogen Peroxide/Peroxidase Assay Kit; Molecular Probes, AlfaGene). Data concerning oxidative stress and NO bioavailability markers have been recently used by our group as part of studies on the same cohort to evaluate the association of these biomarkers with cardiometabolic risk, renal function and angiotensinogen 8,9,30 .…”
Section: Laboratory Proceduresmentioning
confidence: 99%
“…Data concerning oxidative stress and markers of NO bioavailability have been recently used by our group as part of studies on the same cohort to evaluate the association of these biomarkers with cardiometabolic risk, renal function and angiotensinogen [3,21,33].…”
Section: Inflammatory and Oxidative Stress Biomarkersmentioning
confidence: 99%